Macrocyclic lactones inhibit nasopharyngeal carcinoma cells proliferation through PAK1 inhibition and reduce in vivo tumor growth - Gallardo, Franck; Mariamé, Bernard; Gence, Rémi; Tilkin-Mariamé, Anne-Francoise (Drug Design, Development and Therapy, 2018)
International audience Purpose: The Epstein-Barr virus (EBV)-associated cancer nasopharyngeal carcinoma (NPC) is rare in Europe and North America but is a real public health problem in some regions of the world, such as southern Asia, North Africa, and for Inuit populations. Due to the anatomy and location of the nasopharynx, surgery is rarely used to treat primary NPC cancers. Treatment by radiotherapy, combined or not with chemotherapy, are efficient for primary tumors but often do not protect against fatal relapses or metastases. Methods: Search for new therapeutic molecules through high content screening lead to the identification of Ivermectin (IVM) as a promising drug. IVM is a US Food and Drug Administration-approved macrocyclic lactone widely used as anthelmintic and insecticidal agent that has also shown protective effects against cancers. Results: We show here that IVM has cytotoxic activity in vitro against NPC cells, in which it reduces MAPKs pathway activation through the inhibition PAK-1 activity. Moreover, all macrocyclic lactones tested and a PAK1 inhibitor are cytotoxic in vitro for EBV-positive and EBV-negative NPC tumor cells. We have also shown that IVM intraperitoneal repeated injections, at US Food and Drug Administration-approved doses, have no significant toxicity and decrease NPC subcutaneous tumors development in nude mice. Conclusion: Macrocyclic lactones appear as promising molecules against NPC targeting PAK-1 with no detectable adverse effect.